Amazing gorillas! - Thomson, Sarah L.; Wildlife Conservation Society (New York, N.Y.) (New York, NY : HarperCollins, 2005)
Simple text and photographs introduce gorillas to young readers.
"2, reading with help.".
"Wildlife Conservation Society.".
670
Keywords: Gorilla -- Juvenile literature